The promise of public service ideas and examples for effective service - Stahl, Michael M. (New York Routledge, 2023)
In the United States, new government employees begin their careers by pledging their allegiance to the Constitution and by committing to conscientious service dedicated to solving public problems. But what do public servants get in return? For many, a chance to serve provides public servants with a higher purpose as well as professional and personal meaning in their lives and careers. In The Promise of Public Service: Ideas and Examples for Effective Service, Michael M. Stahl, a forty-year veteran in the executive and legislative branches of state and federal service, explores what makes public servants effective by offering useful ideas and examining the accomplishments of public servants throughout American history. The book blends practical ideas and illustrative profiles as Stahl reflects seriously on theoretical frameworks, skillfully synthesizing practical experience with rigorous theoretical and conceptual analysis. Undergraduate and graduate level courses will benefit from The Promise of Public Service as a resource, and practitioners of public service in all its forms will benefit from these ideas and examples at any stage of their careers"--
Introduction: The Oath and the Opportunity -- The Attitude of a Public Servant -- A Reflective Practitioner’s Philosophy: Creating Public Value and Solving Public Problems -- Implementing Public Policy and Using Networks -- Performance-Based Management: An Opportunity Squandered -- Government’s Greatest Achievements -- Qualities Needed by Future Public Servants -- Examples for Effective Public Service: Profiles of Public Service Heroes -- Abraham Lincoln, Keeping the Union Together -- Frederick Douglass, Calling Out the Brutality and Hypocrisy of Slavery -- Ida B. Wells, Journalist Documenting Racial Injustice -- Upton Sinclair, Muckraking Author -- Alice Paul, Fighting for Women’s Voting Rights -- Harry Truman, Plain-Spoken President -- Frances Perkins, Champion of the New Deal -- George Marshall, Rescuing and Restoring Europe -- Martin Luther King, Jr., Warrior for Economic Justice -- Rachel Carson, Mother of a Movement -- Robert Kennedy, Beacon of Hope -- Sergio Vieira De Mello, Diplomat in Harm’s Way Epilogue: Lessons Learned from Public Service Heroes.
Includes bibliographical references and index.
Keywords: Civil service -- United States; United States -- Officials and employees